PENGARUH PERSON ORGANIZATION FIT TERHADAP KOMITMEN ORGANISASIONAL DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI: Studi Kasus Pada Rumah Sakit Daerah Kabupaten Karangasem - I Ketut Mustika; Dewiwati Sujadi; I Komang Sudirgayasa (Universitas Triatma Mulya, 2023)
This study aims to analyze the effect of Person Organization Fit on Organizational Commitment with Job Satisfaction as a mediating variable (Case Study at Regional General Hospital (RSUD) Karangasem Regency). The sampling technique in this study used probability sampling method as many as 148 people. Data analysis techniques use a variance-based or component-based approach with Smart Partial Least Square (PLS). The results of the analysis found that 1) Person organization fit has a positive and significant effect on job satisfaction; 2) Person organization fit has a positive and significant effect on organizational commitment; 3) Job satisfaction has a positive and significant effect on organizational commitment; and 4) Person organization fit has a positive and significant effect on organizational commitment through job satisfaction at the Regional General Hospital of Karangasem Regency. This result means that an increase in Person organization fit will be able to increase organizational commitment through increased job satisfaction at the Regional General Hospital of Karangasem Regency. The suggestion in this study is that hospital management is expected to pay attention to Person organization fit and job satisfaction in an effort to increase employee organizational commitment.